A new species of Hedyselmis Hinton and notes on the phylogeny of the genus (Coleoptera: Elmidae) - Čiampor Jr., Fedor; Čiamporová-Zaÿovičová, Zuzana (Zootaxa, 2008)
A new species, Hedyselmis belatani sp. nov., is described from West Malaysia, based on morphological characters. The description includes detailed drawings of the most important structures. Four fragments of DNA, three mitochondrial (cox1, cob, rrnL) and one nuclear (SSU), were sequenced and compared with H. opis Hinton and other elmid species. The taxonomic position of H. belatani sp. nov., its distribution and the phylogeny of the genus are discussed.